Obsessive Compulsive Disorder in a Woman with Left Basal Ganglia Infarct: A Case Report - Faustino Lopez-Rodriguez; Ibrahim Gunay; Nancy Glaser (Behavioural Neurology)
This report presents a syndrome resembling obsessive convulsive disorder (OCD) secondary to a stroke in the left basal ganglia. The patient's syndrome is virtually identical to those that have been described in bilateral damage of the basal ganglia. However, the stroke described in this case report is located unilaterally in the left basal ganglia. In addition, experience in treating a patient with OCD induced by structural damage of basal ganglia is presented.